ANALYZING THE EFFECTIVENESS OF CONTENT STRATEGIES BY SOCIAL MEDIA INFLUENCERS: A SYSTEMATIC LITERATURE REVIEW - Saputra, Fajar Bayu Setiawan; Srikandi, Melati Budi (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the effectiveness of micro-influencers versus macro-influencers in marketing campaigns. Given the increasing importance of influencer marketing, understanding the optimal deployment of different influencer types is crucial for maximizing campaign impact. While existing research acknowledges the distinct characteristics of micro and macro-influencers, there remains a gap in understanding how their respective strengths align with specific campaign objectives. This research aims to address this gap by analyzing the interplay between engagement, reach, authenticity, cost-effectiveness, and campaign goals. The study employed a systematic literature review using the Scopus database as the primary source. The findings reveal that micro-influencers excel at fostering authentic connections and driving conversions within niche markets due to higher engagement rates, while macro-influencers are better suited for campaigns prioritizing widespread brand awareness due to their extensive reach. Therefore, the selection of micro or macro-influencers, or a combination thereof, should strategically align with campaign goals and budget constraints. Future research should explore the evolving dynamics of influencer marketing in emerging digital landscapes and develop more sophisticated metrics for measuring return on investment.